Efeitos do programa AD-HOMEX nas funções cognitivas, no controle postural e desempenho funcional de idosos com doença de Alzheimer: um ensaio clínico randomizado e controlado - Gomes, Wildja de Lima (2023)
Alzheimer's disease (AD) is a type of neurodegenerative, progressive and irreversible preparation. Physical exercise contributes to neuronal neuroplasticity and induction of neurogenesis in the hippocampus, in addition to improving balance, strength and the number of falls. No studies were found in Brazil that investigated the effect of physical exercise in the home environment with a rigorous study design using home training. Therefore, this thesis comprised three studies. The first aimed to carry out a systematic review to analyze the effect of physical exercise at home on cognitive functions, mobility and muscle strength in elderly people with Alzheimer's. Note that the quality is moderate and the strength of current clinical evidence is low. Thus, there is a need for better designed, randomized, blinded clinical trials, supervised by trained professionals and involving instruments adapted for this population. The study was the basis for the development of a randomized and controlled clinical trial that resulted in two more studies, named as the second and third study in this thesis. The second study aimed to verify the effectiveness of the Home-Based Multimodal Exercise Program (AD-HOMEX) for the improvement of cognitive components and level of physical activity in elderly people with AD. The third study aimed to verify the effectiveness of AD-HOMEX in postural control and functional performance of elderly people with AD. Participants were recruited through a university database, posters and local media. Eligible for this study were 159 elderly people admitted to screening for the clinical diagnosis of AD through the diagnostic criteria, cleared for physical activity and level of disease impairment. Elderly people living in the community, with a clinical diagnosis of AD, able to walk at least 10 meters alone, with a medical certificate with permission to perform physical exercises were included. Cognitive assessment was performed using Addenbrooke's Cognitive Examination-Revised, Frontal Assessment Battery, Trail making Test, Clock Drawing Test, postural control was assessed using the force platform and functional performance was assessed using the Short Physical physical assessment instruments Performance Battery, Foot Eight Walking functional range test and Walking trail making test. Results: The elderly who participated in the AD-HOMEX showed improvement in the cognitive domains of memory, verbal fluency, language and visual-spatial skills and an improvement in the level of physical activity, when compared to the elderly in the control group. However, diversity between groups and moments for the variables of postural control and functional performance were not met. Conclusion: Although the AD-HOMEX program did not generate changes in postural control and functional performance, home training provides advantages for the user and caregivers as it reduces time and expenses with displacement, the elderly with AD remains physically active in a systematic way under the supervision of the AD-HOMEX program. supervision of a professional and the family environment decreases behavioral behavior and spatial disorientation